2013
DOI: 10.1016/j.bpj.2013.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Structural Flexibility of CaV1.2 and CaV2.2 I-II Proximal Linker Fragments in Solution

Abstract: Voltage-dependent calcium channels (CaV) enable the inward flow of calcium currents for a wide range of cells. CaV1 and CaV2 subtype α1 subunits form the conducting pore using four repeated membrane domains connected by intracellular linkers. The domain I-II linker connects to the membrane gate (IS6), forming an α-helix, and is bound to the CaVβ subunit. Previous studies indicated that this region may or may not form a continuous helix depending on the CaV subtype, thereby modulating channel activation and ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…S1). Such high content would promote structural flexibility, as was previously shown in other systems[156]. This trend may have a role in enabling the formation of relatively uniform filaments, despite the varying head lengths.…”
Section: Order and Disorder Of If Terminalssupporting
confidence: 55%
“…S1). Such high content would promote structural flexibility, as was previously shown in other systems[156]. This trend may have a role in enabling the formation of relatively uniform filaments, despite the varying head lengths.…”
Section: Order and Disorder Of If Terminalssupporting
confidence: 55%
“…Increasing flexibility by inserting glycine residues ( 29 , 30 ) decreases channel function. In contrast, decreasing flexibility of this region by removing glycine residues promoted channel function ( 28 , 31 , 79 , 80 ). The presence of a glycine residue proximal to the α-interacting domain in Ca V 1.2 WT could thus explain the requirement of a stronger depolarization in Ca V 1.2 WT versus G449R channels.…”
Section: Discussionmentioning
confidence: 99%
“…The relative rigidity α-helix could promote a strong van der Waals interaction between the guanylate domain of Ca V β and hydrophobic residues of Ca V 1.2 ( 29 , 83 , 84 ). In the native protein, this α-helix breaks at the glycine located at position 449 ( 79 ). Crystallographic and circular dichroism spectroscopic studies demonstrated that the arginine substitution prolongs the α-helix ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A simple SAXS analysis immediately provides R g and the pair distance distribution [63,64]. Additionally, traditional Kratky plots (q 2 I(q) vs. q), directly obtained from the SAXS profiles of IDPs, provide a qualitative picture of the presence of globular or unfolded conformations [65,66]. Here, I is the scattering intensity, and q is the scattered wave-vector proportional to the scattering angle.…”
Section: Saxsmentioning
confidence: 99%